Pengaruh Label Halal Terhadap Minat Beli Obat Bebas dengan Religiusitas sebagai Variabel Moderasi (Studi Kasus Masyarakat Kota Bandung) - Fitriani, Anisa (PT Literasi Nusantara Publisher, 2023)
The aim of this research is to determine the effect of the halal label on interest in buying over-the-counter medicines with religiosity as a moderating variable in the communities of Bandung City. This research used 120 respondents as samples. Data was obtained through distributing questionnaires. The analysis technique used in this research is the Structural Equation Modeling method and for data processing using the SmartPLS 3.0 program. The results obtained are that the halal label has a significant effect on purchase intention, religiosity has a significant effect on purchase intention, while religiosity is not able to moderate the relationship between the halal label and purchase intention.